2021
DOI: 10.1016/j.eclinm.2021.101059
|View full text |Cite
|
Sign up to set email alerts
|

HIV self-testing with digital supports as the new paradigm: A systematic review of global evidence (2010–2021)

Abstract: Background HIV self-testing (HIVST) is recommended by the WHO as an innovative strategy to reach UNAIDS targets to end HIV by 2030. HIVST with digital supports is defined as the use of digital interventions (e.g., website-based, social media, mobile HIVST applications (apps), text messaging (SMS), digital vending machines (digital VMs)) to improve the efficiency and impact of HIVST. HIVST deployment and integration in health services is an emerging priority. We conducted a systematic review aiming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 58 publications
4
43
1
Order By: Relevance
“…How these interventions and linkages to services are best organized in relation to HIVST needs to be further studied, but one potential strategy is implementing HIVST by linking it to existing telemedicine or e-health services, where available, or specially developed digital applications and services. A recent review concluded that HIVST with digital support could improve efficiency of HIVST interventions and is suitable for at-risk populations [ 59 ]. In the literature, there are also specific examples of programs offering HIVST supervised via video chat [ 60 , 61 ], and in Brazil telemedicine was utilized for PrEP in combination with HIVST during Covid-19 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…How these interventions and linkages to services are best organized in relation to HIVST needs to be further studied, but one potential strategy is implementing HIVST by linking it to existing telemedicine or e-health services, where available, or specially developed digital applications and services. A recent review concluded that HIVST with digital support could improve efficiency of HIVST interventions and is suitable for at-risk populations [ 59 ]. In the literature, there are also specific examples of programs offering HIVST supervised via video chat [ 60 , 61 ], and in Brazil telemedicine was utilized for PrEP in combination with HIVST during Covid-19 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the opinions of MSM recruited in online gay dating websites and apps in Spain, acceptability and potential use of HIV self-testing is high [18] and it is a highly valued option [19]. In fact, several clinical trials also support self-testing's capacity to increase testing frequency among MSM and other highly vulnerable populations [20,21] but there is little real-life data on its capacity to promote testing. This is challenging since HIV statistics do not reflect the setting where HIV testing is occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding end users’ needs and preferences is critical in guiding effective HIVST interventions [ 38 ]. When planning HIVST programs among young people, implementers should be attentive to the packaging and instructions for the HIVST kits to be custom-made to the youths’ needs and local literacy levels and context [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%